EXPLORING TIKTOK AS DIGITAL TOOL FOR ENGLISH LANGUAGE TEACHING AND LEARNING - Miftahul Jannah; Dia Amara Rasidin (Teaching and General Education Studies, 2026)
The increasing use of social media has opened new possibilities for English language learning in the digital era. Among various platforms, TikTok has attracted significant attention because of its interactive and engaging features that support language learning. This review examines studies published between 2020 and 2024 to explore the role of TikTok in English language education. The findings show that TikTok can help learners improve vocabulary, speaking skills, and pronunciation through short videos, repeated exposure to language, and interactive activities such as duet challenges. These features create an enjoyable learning environment and encourage active participation among learners. The platform also provides authentic language input that can enhance students’ motivation and confidence in using English. However, several challenges limit its classroom implementation, including its entertainment-focused algorithm, limited depth of educational content, unequal access to technology, and differences in teachers’ digital competence. Overall, TikTok has emerged as a useful supplementary tool that can support English language learning when used appropriately.